Generalized and pregnancy-related anxiety prevalence and predictors among pregnant women attending primary health care in Qatar, 2018–2019 - Sarah Naja (9954737) (2020)
Background Cumulative evidence suggests that early identification of anxiety in pregnancy is important, given that antenatal anxiety has been linked to morbid outcomes in expecting mothers and their offspring. However, the burden of antenatal anxiety is not yet known in Qatar. This research aims to measure the prevalence and determinants of generalized and pregnancy-related anxiety among pregnant women. Methods Eight hundred pregnant women completed a structured interview and self-administrated questionnaires after being selected through probability sampling from nine primary healthcare centers distributed across Qatar. We subjected the data to Binary and Multiple Logistic Regression Analysis. Furthermore, we conducted a Confirmatory Factor Analysis for the utilized scales. Results Out of eight hundred participants, 26.5% reported high pregnancy-related anxiety, while 16.4% had a generalized anxiety disorder. A high level of perceived social support and resilience was shown to mitigate generalized and pregnancy-related anxiety. However, we revealed that different determinants influence the two types of anxiety. Limitations There is no recognized optimal cut-off point to distinguish ‘high risk’ in pregnancy-related anxiety scales. Conclusions Pregnancy-related anxiety is more prevalent than generalized anxiety among pregnant women in Qatar, indicating that stakeholders must include screening for pregnancy-related anxiety in Qatar's clinical guidelines. Tailored interventional studies could focus on increasing resilience and social support to decrease the burden of antenatal anxiety. Other Information Published in: Heliyon License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.heliyon.2020.e05264